Analisis Karakteristik Budaya Organisasi dan Kinerja Karyawan di PT Mitra Lintas Nusantara - Hendrawan Saputra; Raden Kelik Hardinto; Linda Permanasari; Agus Pebrianto (BIMA: Jurnal Bisnis dan Manajemen, 2023)
The purpose of this study was to determine the characteristics of the organizational culture at PT Mitra Lintas Nusantara Banjarmasin and also to determine the performance characteristics of the employees working at PT Mitra Lintas Nusantara Banjarmasin. Descriptive research approach method where descriptive research is research that is used to describe or analyze a research result but is not used to make broader conclusions as the scientific method is often used and carried out by a group of researchers in the social sciences, including education science. This descriptive study was chosen by the author to describe the characteristics of organizational culture and employee performance at PT Mitra Lintas Nusantara Banjarmasin. The results of this study found that the characteristics of organizational culture at PT Mitra Lintas Nusantara Banjarmasin have several points that must make adjustments and developments in order to be in accordance with the theory, while for the performance characteristics of employees at PT Mitra Lintas Nusantara Banjarmasin already meet the elements of the theory of employee performance characteristics. when compared with the results of existing questionnaires